2019
DOI: 10.1021/acs.energyfuels.9b03571
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ketone and Surfactant for Enhancement of Water Imbibition in Fractured Porous Media

Abstract: This paper presents a comparative study of two wettability modifiers with different characteristics for enhancing water imbibition from a fracture into the surrounding matrix. One is 3-pentanone, a symmetric short ketone, and the other is 2-ethylhexanol–4 propylene oxide–15 ethylene oxide, a non-ionic surfactant with an ultrashort hydrophobe. They were used as low-concentration additives (approximately 1 wt %) to reservoir brine in this research. The coreflooding experiments using fractured limestone cores sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…5 Therefore, imbibition recovery and its rate can be enhanced when surfactants are optimally applied. 147,148 A study showed that 10 surfactant imbibition tests provided 15.7−25.4% imbibition recovery and 4 surfactant imbibition tests provided 6.8−10.2% imbibition recovery; their incremental recoveries are over brine imbibition. 145 Panels a 45 and b 118 of Figures 22 show that imbibition recovery increases when surfactants are applied, and its incremental degree is related to the types and concentrations of surfactants and the characteristics of reservoirs.…”
Section: Eor By Imbibition In Reservoir Developmentmentioning
confidence: 99%
“…5 Therefore, imbibition recovery and its rate can be enhanced when surfactants are optimally applied. 147,148 A study showed that 10 surfactant imbibition tests provided 15.7−25.4% imbibition recovery and 4 surfactant imbibition tests provided 6.8−10.2% imbibition recovery; their incremental recoveries are over brine imbibition. 145 Panels a 45 and b 118 of Figures 22 show that imbibition recovery increases when surfactants are applied, and its incremental degree is related to the types and concentrations of surfactants and the characteristics of reservoirs.…”
Section: Eor By Imbibition In Reservoir Developmentmentioning
confidence: 99%
“…in length and 1 in. in diameter and Amott cells at 338 K. The experiments largely followed the procedure described by Wang et al , The limestone cores were prepared through core-flooding experiments by first saturating the cores with crude oil and then measuring core properties, such as porosity, permeability, water saturation, and oil saturation Table summarizes the measured core properties for the core samples used in the imbibition experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The partition behavior of surfactants between an aqueous surfactant solution and crude oil has been widely studied to determine the performance of surfactants during surfactant flooding chemical EOR. ,, Different surfactants have different partition coefficients depending upon their solubility in both phases (surfactants can partition into both the aqueous and oleic phases). As wettability modifiers, however, the surfactant solution lowers the water/oil IFT, while the 3-pentanone solution does not …”
Section: Introductionmentioning
confidence: 99%
“…Recently, short-hydrophobe surfactants were studied by several researchers. Wang et al tested a short-hydrophobe surfactant as a wettability modifier for oil recovery from fractured limestone cores . They found that 2-etheylhexanol-4PO-15EO (or 2-EH-4PO-15EO) altered the wettability of calcite surfaces from oil-wet (contact angle: 134.1°) to water-wet (contact angle: 47.1°) after 1 day.…”
Section: Introductionmentioning
confidence: 99%
“…7−9 Wang et al tested a short-hydrophobe surfactant as a wettability modifier for oil recovery from fractured limestone cores. 7 4PO-15EO (or 2-EH-4PO-15EO) altered the wettability of calcite surfaces from oil-wet (contact angle: 134.1°) to waterwet (contact angle: 47.1°) after 1 day. Then, they conducted dynamic imbibition tests for oil recovery from fractured limestone cores.…”
Section: Introductionmentioning
confidence: 99%